Patient exposure data and operator dose in coronary interventional procedures: Impact of body-mass index and procedure complexity. (August 2020) - Zanca, Federica; Collard, Celine; Alexandre, Nicolas; Deprez, Frédéric; Salembier, Jean Paul; Henry, Michel; Rombaut, Emmanuel; Massart, Pierre-Emmanuel
Graphical abstract: Left: PKA values stratified per BMI classes for CA (1) and PCI (2) procedures. Right: Comparison of the Fluoroscopy Time per range of Complexity Index (CI) for the PCI procedures. Number of cases and median values are reported. One-Sentence Summary: Dose references levels for PKA and Fluoroscopy Time in interventional cardiology should be defined in function of BMI classes and Complexity Index. These could provide an additional tool for refining a facility's quality assurance and optimization processes. Highlights: Total air kerma area product (PKA ) and fluoroscopy time (FT) increase with BMI and procedure complexity index (CI). Significant PKA variability was observed among cardiologists for CA (p<0.001) but not for PCI procedures. Dose references levels for PKA and FT in interventional cardiology should be defined in function of CI and BMI class. These findings could provide an additional tool for refining a facility's quality assurance and optimization processes. Abstract: Purpose: The aim of this study was to assess patient exposure data and operator dose in coronary interventional procedures, when considering patient body-mass index and procedure complexity. Methods: Total air kerma area product (PKA ), Air-Kerma (AK), Fluoroscopy time (FT), operator dose and patient body-mass index (BMI) from 97 patients' procedures (62 coronary angiography (CA) and 35 Percutaneous Coronary Intervention (PCI) were collected for one year. For PCI procedures, also the complexity index-CI was collected. Continuous variables for each of the 2 groups procedures (CA and PCI) were compared as medians with interquartile range and using Mann-Whitney U test. Multiple group data were compared using Kruskal-Wallis test (significance: p < 0.05). Results: Median PKA was 63 and 125 Gy cm 2 for CA and PCI respectively (p < 0.001); FT was 3 and 14 min, respectively (p < 0.001). PKA and FT significantly increased (p < 0.05) with BMI class for CA procedures. PKA and FT also increased in function of CI class for PCI, thought significantly only for FT (p < 0.001), possibly because of the low number of PCI procedures included; cine mode contributed most to PKA . Significant dose variability was observed among cardiologists for CA procedures (p < 0.001). Conclusions: Dose references levels for PKA and FT in interventional cardiology should be defined - on a sufficient number of procedures- in function of CI and BMI classes. These could provide an additional tool for refining a facility's quality assurance and optimization processes. Dose variability associated with cardiologists underlines the importance of continuous training.